HUBUNGAN TIPE KEPRIBADIAN DENGAN KOMUNIKASI INTERPERSONAL MENANTU PEREMPUAN TERHADAP IBU MERTUA - Josefine Ayu Kinanti; Fabiola Hendrati (University of Merdeka Malang, 2013)
Abstract The purpose of this study was to determine the relationship of personality type with interpersonal communication daughter against mother-in-law. The research sample that is 106 people in the village Pandanlandung daughter Malang. Sampling technique using purposive sampling. Methods of data collection using the Likert method for interpersonal communication daughter against mother-in-law and the big five personality types, details the scale of interpersonal communication daughter against mother-in-law 60 aitem and big five personality types 44 aitem. The results of the data analysis using Pearson's product moment correlation showed that extraversion count r = 0.320 and r = 0.256 in table 1% significance level at which a count r 0.320 0.256 r table means the hypothesis is accepted. count r = 0.260 and r agreeableness table = 0.256 at a significance level of 1% which, if r count 0.260 0.256 r table means the hypothesis is accepted. count r = 0.085 and r conscientiousness table = 0.195 at a significance level of 5% which if counted 0.085 r 0.195 r table means the hypothesis is rejected. count r = -0.043 and r neuroticism table = 0.195 at a significance level of 5% -0.043 count where if r r 0.195 table means the hypothesis is rejected. r count openness to new experience = 0.210 and r = 0.195 in table 5% significance level at which a count r 0.210 0.195 r table means the hypothesis is accepted.